Pengaruh Tuntutan Pekerjaan dan Efikasi Diri Okupasional Terhadap Kesejahteraan Karyawan PT. X Sektor Energi - Dinarwati, Enny; Eflina Purba, Debora (Psyche 165 Journal, 2023)
The company is working to improve financial performance and achieve profitability, not only by reducing costs, restructuring, and delaying the recruitment of new employees, but also by working on various new projects for business growth that have a negative impact on employee well-being. Increased job demands are associated with decreased employee well-being. At the same time, occupational self-efficacy possessed by employees can improve employee well-being. This study aims to analyze the relative contribution of job demands and occupational self-efficacy to employee well-being at PT.X Energy Sector. The research method used in this research is a quantitative approach with a correlational research type. The number of samples in this study were 114 people. The research sample was taken using a convenience sampling technique, with the criteria of participants having worked for at least 1 year. The participants who filled out the questionnaire were 100 people, with a response rate of 88%. The research instrument used was the Warr scale instrument and the measurement of job demands used the Questionnaire on the Experience and Evaluation of Work 2.0 (QEEW 2.0) scale obtained from previous research. Based on the results of multiple regression analysis using the stepwise method in SPSS, it is concluded that job demands contributed to a decrease in the level of employee well-being by 26.6%. Taken together, job demands and occupational self-efficacy contribute to employee well-being by 43.3%. The results also show that occupational self-efficacy has a unique contribution to improving employee well-being by 16.7%. The implication of this result study is that company need to pay attention to the employee’s workload and at the same time also increase employee competence so that confidence in their ability to do their job increases.